2021
DOI: 10.2169/internalmedicine.7336-21
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Eicosapentaenoic Acid to Arachidonic Acid Ratio on Long-term Cardiovascular Events Following Percutaneous Coronary Intervention

Abstract: Objective The relationship between cardiovascular disease and the serum polyunsaturated fatty acid parameters has been reported. The aim of the present study was to investigate the association between the eicosapentaenoic acid and arachidonic acid (EPA/AA) ratio and long-term cardiovascular events in patients with coronary artery disease. Methods We identified a total of 831 patients who underwent percutaneous coronary intervention and whose EPA/AA ratio was available. The patients were divided into two groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…In a Japanese community, the serum EPA/arachidonic acid (AA) ratio decreased over 10 years 2) . Previous studies showed that a lower serum EPA/AA ratio is predictive of the incidence of cardiovascular events [3][4][5][6] . The JELIS and REDUCE-IT trials verified that highly purified EPA ethyl ester (EPA-E) reduced the risk of cardiovascular events 7,8) .…”
Section: Introductionmentioning
confidence: 99%
“…In a Japanese community, the serum EPA/arachidonic acid (AA) ratio decreased over 10 years 2) . Previous studies showed that a lower serum EPA/AA ratio is predictive of the incidence of cardiovascular events [3][4][5][6] . The JELIS and REDUCE-IT trials verified that highly purified EPA ethyl ester (EPA-E) reduced the risk of cardiovascular events 7,8) .…”
Section: Introductionmentioning
confidence: 99%